Exploring Determinants of Sexual Satisfaction in a Chilean Representative Sample - Cespedes-Carreno, C (Routledge, 2021)
This article examines the relationship between sexual satisfaction and gender, age, social status, being in stable relationships, intercourse frequency, and satisfaction with physical attractiveness (physical appearance and sex appeal). A self-report questionnaire was applied in a representative sample of 767 residents of Santiago (Chile), over 18 years old and that have had, at least, one sexual relation (with penetration) during their lives. Higher sexual satisfaction was predicted negatively by age and positively by higher satisfaction with sex appeal, higher intercourse frequency and having a stable relationship. Among women, the principal predictors are satisfaction with sex appeal and intercourse frequency. Among men to the above, it is necessary to add satisfaction with physical appearance and having a stable relationship–at odds with supposed higher relevance for women of body satisfaction and sensibility to social relationships. Discussion emphasizes the controversial nature of the gender differences found regarding the Latin American culture. © 2020 Taylor & Francis Group, LLC.